The Contribution of Working Memory Areas to Verbal Learning and Recall in Primary Progressive Aphasia - Afthinos, Alexandros; Themistocleous, Charalambos; Herrmann, Olivia; Fan, Hongli; Lu, Hanzhang; Tsapkini, Kyrana (Frontiers in Neurology, 2022)
Recent evidence of domain-specific working memory (WM) systems has identified areas and networks which are involved in phonological, orthographic, and semantic WM, as well as higher level domain-general WM functions. The contribution of these areas throughout the process of verbal learning and recall is still unclear. In the present study we asked, what is the contribution of domain-specific specialized WM systems in the course of verbal learning and recall? To answer this question, we regressed perfusion data from pseudo-continuous arterial spin labeling (pCASL) MRI with all immediate, consecutive, and delayed recall stages of the Rey Auditory Verbal Learning Test (RAVLT) from a group of patients with Primary Progressive Aphasia (PPA), a neurodegenerative syndrome in which language is the primary deficit. We found that the early stages of verbal learning involve areas subserving phonological processing (left superior temporal gyrus) as well as semantic WM memory (left angular gyrus, AG_L). As learning unfolds, areas subserving semantic WM (AG_L) as well as lexical/semantic (inferior temporal and fusiform gyri, temporal pole) and episodic memory (hippocampal complex) become more involved. Finally, delayed recall depends entirely on semantic and episodic memory areas (hippocampal complex, temporal pole and gyri). Our results suggest that AG_L subserving domain-specific (semantic) WM is involved only during verbal learning, but delayed recall depends only on medial and cortical temporal areas.